Course Hero Logo

203_Assignment3_Solutions.pdf - COS4807/203/0/2021 Tutorial...

Course Hero uses AI to attempt to automatically extract content from documents to surface to you and others so you can study better, e.g., in search results, to enrich docs, and more. This preview shows page 1 - 3 out of 7 pages.

Define Tomorrow.universityof south africaTutorial Letter 203/0/2021Formal LogicCOS4807Year moduleDepartment of Computer ScienceSchool of ComputingCONTENTSSolutions to Assignment 3COS4807/203/0/2021
SOLUTIONS TO ASSIGNMENT 3Question 1(20)(i) To prove that the formulaxyp(x, y)→ ∀yxp(x, y) is valid, we must show that it is true inall interpretations. We do this by contradiction.Say there is an interpretationIin which the formula is false, i.e.vI(xyp(x, y)→ ∀yxp(x, y)) =F. ThenvI(xy(p(x, y)) =TandvI(yxp(x, y)) =F(by the truth values of implication).ThenvσI(yp(x, y)) =Tfor some assignmentσIandvσ0I(xp(x, y)) =Ffor some assignmentσ0I(both by Theorem 7.22).According to Definition 7.18,σImaps the only free variable inyp(x, y), namelyx, to a valuedD.SincevσI(yp(x, y)) =T, according to Definition 7.19vσI[yei](p(x, y)) =Tfor alleiD.Also according to Definition 7.18,σ0Imaps the only free variable inxp(x, y), namelyy, to avalueeD. Sincevσ0I(xp(x, y)) =F, according to Definition 7.19vσ0I[xdj](p(x, y)) =FforalldjD.But this is a contradiction because by Definition 7.19 the ordered pair (d, e) must be inRp(the relation assigned topinI) to comply withvσI[yei](p(x, y)) =Tfor somedDand alleiD, but (d, e) may not be inRpto comply withvσ0I[xdj](p(x, y)) =Ffor someeDandalldjD.So our assumption, namely that there is an interpretationIin which the formula is false, isincorrect, and we conclude that the formula is valid.BTW, as proved in Question 2, the converse of this formula is not valid. See if you can workout why a validity proof similar to the above won’t work.(ii) To prove thatx(p(x)q(x))(xp(x)∧ ∀x¬q(x)) is unsatisfiable, we must show that it isfalse in all interpretations.LetIbe an arbitrary interpretation of the formula.vI(x(p(x)q(x))) =FiffvσI(p(x)q(x)) =Ffor all assignmentsσI(by the semantics of)iffvσI(p(x)) =TandvσI(q(x)) =Ffor all assignmentsσI(by the truth values for implication)iffvσI(p(x)) =TandvσI(¬q(x)) =Tfor all assignmentsσI(by the truth values for negation)iffvI(xp(x)) =TandvI(x¬q(x)) =T(by the semantics of)iffvI(xp(x)∧ ∀x¬q(x)) =T(by the truth values of conjunction)SincevI(x(p(x)q(x)) =FiffvI(xp(x)∧ ∀x¬q(x)) =T, we conclude thatvI(x(p(x)q(x))6=vI(xp(x)∧ ∀x¬q(x)), and thus that

Upload your study docs or become a

Course Hero member to access this document

Upload your study docs or become a

Course Hero member to access this document

End of preview. Want to read all 7 pages?

Upload your study docs or become a

Course Hero member to access this document

Term
Summer
Professor
N/A
Tags

Newly uploaded documents

Show More

Newly uploaded documents

Show More

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture